Quantitative biochemical screening for marijuana use and concordance with tobacco use in urban adolescents. (1st December 2019) - Benowitz, Neal; Nardone, Natalie; St.Helen, Gideon; Addo, Newton; Jacob, Peyton; Liakoni, Evangelia; Jain, Shonul; Hooshfar, Shirin; Lynch, Kara
Highlights: There is known to be a high concordance of tobacco and marijuana use in adolescents. Co-use has been demonstrated to increase risk of addiction and mental illness. Biochemical analysis of adolescent urine confirms a high biomarker concordance. Correlation between nicotine and THC exposure levels in youth is further quantified. Novel data suggests a strong predictive value of smoking tobacco in marijuana use. Abstract: Background: Assessing the prevalence and level of exposure (dose) of tobacco and marijuana use is important in studies of harm from use of these substances. We used biochemical analysis of urine to quantitatively assess exposure to nicotine and delta 9-tetrahydrocannabinol (THC) in adolescents receiving medical care in a public hospital Methods: Participants were 686 adolescents between 12 and 21 years old seen at Zuckerberg San Francisco General Hospital between 2012 and 2014. Urine samples were assayed using high sensitivity liquid chromatographic assays for cotinine, a major metabolite of nicotine, and 11-nor-9-carboxy-delta 9-THC (THC−COOH), a major metabolite of THC. A commonly used immunoassay screen for THC−COOH was also performed. Results: The THC−COOH immunoassay substantially underestimated THC exposure, as measured with the high sensitivity assay. THC use was detected in 25% of participants, with higher prevalence with increasing age and in non-Hispanic blacks. Active tobacco smokers had an 80% prevalence of THC use (odds ratio for cigarette smoking predicting THC use 13.2). Urine cotinine and THC−COOH were significantly correlated (r = 0.60). Conclusions: The use of a high sensitivity chromatographic urine assay provides a much more complete picture of adolescent tobacco use compared to a commonly used immunoassay. The immunoassay provides high specificity but moderate sensitivity. We confirm high concordance of tobacco and marijuana use and the high predictive value of cigarette smoking in predicting marijuana use, and provide novel data on the quantitative correlation between level of exposure to nicotine and THC. Quantitative screening of nicotine and THC exposure may enhance our understanding of addiction and harm from single and dual product use.